Daytime shooting star. 6 - Yamamori, Mika (Shojo beat manga., 2020)
"Suzume has moved to Tokyo and is living with her uncle. With Mr. Shishio's true feelings for her out in the open, Suzume tries her best to figure out if they are an item or not. Meanwhile, Mamura grows suspicious of Shishio and Suzume's relationship."--Provided by publisher.